Effect of solvent on α-SnWO4 photocatalyst for degradation of methyl orange under visible light irradiation. (July 2015) - Wang, Q. L.; Li, H. B.; Jiang, H. Y.; Ding, S. T.; Song, Z. W.; Shi, J. S.
Abstract : α-SnWO4 photocatalysts were prepared in different solvent mediated conditions via a solvothermal method. The effects of solvents on the morphology and structure of the products were investigated by means of X-ray diffraction, SEM, TEM, Brunauer–Emmett–Teller, and UV—visible techniques. The results indicate that the samples with various morphologies, different surface areas, pore parameters and bandgap energies can be obtained. Photocatalytic test shows ethylene glycol mediated α-SnWO4 nanosheets exhibited the highest photocatalytic activity for its degradation of methyl orange compared with aqueous, diluted hydrochloric acid, methanol and ethanol mediated samples. In addition, ethylene glycol mediated α-SnWO4 was measured to be stable while undergoing the photocatalytic process. These results suggest that, the solvent in the synthetic system is one of the important factors tuning the microstructure, morphology, surface area and purity of α-SnWO4 powders, and hence affects the optical absorption performance and photocatalytic activity.